Efektivitas Model Numbered Heads Together Terhadap Minat Belajar pada Mata Pelajaran IPA Kelas IV SD - Yuniarti, Yuniarti; Hermansyah, Hermansyah; Selegi, Susanti Faipri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of the study was to determine the effectiveness of Numbered Heads Together model on the learning interest in science subject for IV grade elementary school. The experimental method was used in this study. The population in this study were all IV grade students at SD Negeri 1 RambangKuang. The samples were class IV A as the experimental class and class IV B. Data analysis was conducted by analizingnormality data and homogeneity. The result showed that the average score obtained in pre-test for the experimental class was 77.31 and the post-test average scorefor the experimental class was 83.31. While the average score for the control class pre-test was 55.68 and the post-test average score for control classwas 62.72. 2) Based on the results of the t-test obtained = 15.62 and 1.721, meaning > = 15.62 > 1.721 then Ha was accepted and Ho was rejected. So it could be concluded that the Numbered Heads Together model is effectively used in increasing student interest in learning, this was proven by the student learning outcomes in science subjects that used theNumbered Heads Together model which was higher than the learning outcomes used the conventional model. It was recommended that during the learning process the teacher should be able to create a pleasant learning atmosphere and involve the activities of all students.